2010
DOI: 10.1042/cs20100053
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the renin–angiotensin system prevents seizures in a rat model of epilepsy

Abstract: The RAS (renin-angiotensin system) is classically involved in BP (blood pressure) regulation and water-electrolyte balance, and in the central nervous system it has been mostly associated with homoeostatic processes, such as thirst, hormone secretion and thermoregulation. Epilepsies are chronic neurological disorders characterized by recurrent epileptic seizures that affect 1-3% of the world's population, and the most commonly used anticonvulsants are described to be effective in approx. 70% of the population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 30 publications
1
65
1
1
Order By: Relevance
“…However, results using inhibition of ACE and antagonists of AngII receptors suggest a pro-convulsant action of AngII in the brain. AngII receptor antagonists showed anti-convulsant affects in pentylenetetrazol treated rats [248] and both AngII receptor antagonists and ACE antagonists attenuated audiogenic seizures [242]. Moreover, the effects of known antiepileptics were potentiated by AngII receptor antagonists in electroshock seizures [249,250] and by ACE inhibitors in audiogenic seizures [251].…”
Section: Angiotensinsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, results using inhibition of ACE and antagonists of AngII receptors suggest a pro-convulsant action of AngII in the brain. AngII receptor antagonists showed anti-convulsant affects in pentylenetetrazol treated rats [248] and both AngII receptor antagonists and ACE antagonists attenuated audiogenic seizures [242]. Moreover, the effects of known antiepileptics were potentiated by AngII receptor antagonists in electroshock seizures [249,250] and by ACE inhibitors in audiogenic seizures [251].…”
Section: Angiotensinsmentioning
confidence: 89%
“…Originally described in the hypothalamus related to the control of fluid intake [237], the RAS has also been identified in other brain regions, too, including the cortex and the hippocampus [238][239][240]. Furthermore, the levels of components of the RAS were changed in the hippocampus following pilocarpine treatment of rats [241] and audiogenic seizures [242] as well as in human temporal lobe epilepsy [243]. Initial studies of a research group suggested anti-convulsant actions of Ang peptides against pentylenetetrazol-induced seizures [244] reviewed recently [245].…”
Section: Angiotensinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, treatment with losartan (AT 1 receptor antagonist) was capable of decreasing the severity of seizures of WARs with TLE. 28 On the basis of those studies, we aimed to investigate the metabolism of AngI in the hippocampus and related enzymatic pathways. We first show that Ang-(1-7) is the AngI metabolite that is preferentially generated by hippocampal enzymes; second, we show that TOP is one of the major enzymes involved in the AngI metabolism, and it is responsible for ≈50% of the Ang-(1-7) formation in the hippocampus.…”
Section: Hypertensionmentioning
confidence: 99%
“…8 In a rat model of epilepsy, it was found that components of the RAS, namely ACE and the AT1 receptors are up-regulated in the brain following repetitive seizures. 9 Angiotensin has also been shown to modulate the voltage dependent delayed rectifier potassium current (IK) and IA. 10 Reports suggest higher incidence of seizures in presence of pre-existing chronic inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%